The Alcalar Study: A Quality Of Life Comparative Study On Institutionalised Elderly - Malveiro, Jorge A.; de Jesus, Saul Neves; Rego, Rui (Journal of Tourism, Sustainability and Well-being, 2017)
Summary: Comparative evaluation on Quality of Life (QoL) perception on different communitarian residential institutional environments for senior citizens. Method: Cross-sectional comparative study, using a deductive and a descriptive statistical method on a sample of 50 senior citizens inhabitants in the Retirement-village St. Joseph of Alcalar (Alcalar group), 56 senior residents in traditional retirement homes (RSS group) and on 52 senior attendees of day care institutions (DCI group). This research comprised on two self-applicable questioners for elderly citizens on WHOQOL-BREF e WHOQOL-Old PT. We evaluated 158 senior citizens selected from 22 Institutions. Results: QoL levels perceived by Alcalar Retirement-village inhabitants were predominantly higher than QoL levels perceived by residents in RSS and DCI attendees. The trend in QoL results obtained by the Alcalar Retirement-village inhabitants just wasn’t absolute because they were overcome by DCI attendees results in some (few) areas assessed in both WHOQOL scales. Conclusion: The Alcalar Retirement-village group globally showed higher levels of Quality of Life perception by comparison with the other two group subjects’ residents and attendees, respectively, from RSS and DCI.